{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

MECH 213 - 9.28.07

# MECH 213 - 9.28.07 - Qdot b,Act = mdot b c pb(T b2 – T b1...

This preview shows pages 1–2. Sign up to view the full content.

MECH 213 – September 28, 2007 Heat exchangers (HX) What it is o a pipe surrounded by a pipe o two distinct fluids that do not mix First Law o If the system includes both pipes Qdot – Wdot = Σ(mdot*θ) out – Σ(mdot*θ) in Fluid A = mdot a Fluid B = mdot b Δke ≈ 0 Δpe ≈ 0 0 = Σ(mdot*h) out – Σ(mdot*h) in 0 = (mdot a *h a2 + mdot b *h b2 ) – (mdot a *h a1 + mdot b *h b1 ) 0 = mdot a (h a2 – h a1 ) + mdot b (h b2 – h b1 ) o Also called enthalpy balance o System A only Qdot a = mdot a (h a2 – h a1 ) o System B only Qdot b = mdot b (h b2 – h b1 ) o Both A & B -Qdot a = Qdot b o Δh = c p ΔT 0 = mdot a c pa (T a2 – T a1 ) + mdot b c pb (T b2 – T b1 ) if the fluids have equal mdot*c p the temperature gain in one is the same as the loss in the other thermal capacity = mdot*c p o Regenerator – heat exchanger that reuses waste heat o Effectiveness – determines how well a heat exchanger operates (not in text) ε ≡ Qdot ACTUAL /Qdot MAX must be between 0 and 1 will be the same for both fluids

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Qdot b,Act = mdot b c pb (T b2 – T b1 ) Qdot b,Max = mdot b c pb (T a1 – T b1 ) Mixing Chamber (MX) o Does exactly the same thing as a heat exchanger except that the two fluids leave the same outlet at the same temperature o Example – faucet (hot & cold water) o 0 = (mdot A + mdot B )h 2 – mdot a h a1 – mdot b h b1 o B A A mdot A + mdot b B Tubing and piping o Tubing – cylinder inside an object Usually very thick to prevent breaking o Piping – cylinder that connects an object externally to something else 1 2 Pipe Qdot – Wdot = mdot(Δh + Δke + Δpe) 0 = mdot(h 2 – h 1 + (V 2 2 – V 1 2 )/2 + g(z 2 – z 1 ) 0 = (p 2 – p 1 )/ρ + (V 2 2 – V 1 2 )/2 + g(z 2 – z 1 ) Bernoulli’s Principle p 1 /ρ + V 1 2 /2 + gz 1 = p 2 /ρ + V 2 2 /2 + gz 2...
View Full Document

{[ snackBarMessage ]}